2021
DOI: 10.1177/13623613211016729
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of school-based services for students with autism: Barriers and facilitators across urban and rural districts and phases of implementation

Abstract: Research regarding variables influencing evidence-based practice implementation within school services for students with autism spectrum disorder is limited. Using qualitative methods, the current study applies the Exploration, Preparation, Implementation, and Sustainment framework to characterize factors impacting the implementation of practices for students with autism spectrum disorder across urban and rural school districts. The guiding questions of the study include: (1) Are contextual factors perceived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…The other inner context variables were not associated with the IIdx. Previous literature and program developers have suggested that teachers’ attitudes and beliefs about EBPs are associated with implementation (Drahota et al, 2012; Locke et al, 2019; Suhrheinrich et al, 2021). This association was not found in the current study, which does not mean that the relationship is not important or does not exist in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The other inner context variables were not associated with the IIdx. Previous literature and program developers have suggested that teachers’ attitudes and beliefs about EBPs are associated with implementation (Drahota et al, 2012; Locke et al, 2019; Suhrheinrich et al, 2021). This association was not found in the current study, which does not mean that the relationship is not important or does not exist in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…For linkages between provider attitudes and EBP uptake, the evidence has been strong in healthcare settings ( Aarons et al, 2009 ; Becker-Haimes et al, 2017 ; Beidas et al, 2014 ; Farahnak et al, 2020 ), but mixed in school settings ( Locke, Lawson, et al, 2019 ; Odom et al, 2022 ; Suhrheinrich et al, 2020 ). In the context of special education teachers and staff serving elementary-aged students with autism spectrum disorder, for example, one study found that positive attitudes toward EBPs were significantly associated with the intensity of use for only one of three EBPs examined ( Locke, Lawson, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Related to mental health, research has established that principal buy-in and school leadership are critically important to the implementation of universal prevention programs [ 58 61 ]. Other studies are examining leadership in relation to implementation of interventions for autism spectrum disorders [ 8 , 17 , 18 , 62 , 63 ] and characterizing leadership styles conducive to implementation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%